1983
DOI: 10.1111/j.1460-2695.1983.tb00351.x
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Study of the Crack Closure Effect on Near‐threshold Fatigue Crack Growth

Abstract: Crack closure in the near-crack-tip region has been considered to be an important contribution to the development of a crack-growth threshold for rnacroscopic cracks. Recent analytical work, however. has suggested that closure well back of the tip may be the controlling factor. In order to check on this possibility, material has been machined away far behind the crack tip in order to eliminate long-range closure. Removal of this material did not eliminate the threshold, but did lower the threshold level by app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…The shape and configuration of this insert, as depicted in Fig. 1, is in agreement with the general increase in the residual material with increasing AK and the reported results concerning the effect of crack wake removal on the closure load [6,7].…”
Section: R4supporting
confidence: 75%
See 1 more Smart Citation
“…The shape and configuration of this insert, as depicted in Fig. 1, is in agreement with the general increase in the residual material with increasing AK and the reported results concerning the effect of crack wake removal on the closure load [6,7].…”
Section: R4supporting
confidence: 75%
“…where a is the crack length, E is the Young's modulus, W is the width, r is the uncracked segment or the remainder of the specimen, d is the distance between the load line and the knife edges, and f(a/W) is: 6 …”
Section: R4mentioning
confidence: 99%
“…1. Subsequent work by Minakawa et al on a powder metallurgy aluminium alloy [23] was aimed at further examination of this effect. An electro-discharge machining technique (EDM) was utilised to remove part of the crack wake.…”
Section: Crack Wake Closurementioning
confidence: 98%
“…Several researchers have recently questioned the effects that the details of any particular testing scheme may have on the measured threshold [22,23]. Load shedding produces a distribution of residual plastic strains in the wake of the crack, and these become larger with increasing distance behind the crack tip.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that crack closure is a function of crack wake length [10]. Zaiken and Ritchie [11] as well as others [12,13] have shown that in the near-threshold regime where roughness induced closure is important, removal of crack wake reduces closure. However, the influence of crack wake is unknown at higher stress intensities where plasticity induced closure is dominant.…”
mentioning
confidence: 99%